2018
DOI: 10.21561/jor.2018.3.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for a Favorable Response to Intravitreal Bevacizumab for Macular Edema Associated with Branch Retinal Vein Occlusion

Abstract: Purpose: To determine the factors for predicting a favorable response to intravitreal bevacizumab (IVB) for macular edema (ME) associated with branch retinal vein occlusion (BRVO). Methods: Thirty-seven eyes of patients first diagnosed with BRVO-associated ME and treated with IVB more than twice were included in this retrospective case series. Baseline characteristics, initial best-corrected visual acuity (BCVA), initial central macular thickness (CMT), and change in CMT after 2 consecutive monthly IVB injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Predicting visual function and recurrence of ME is important when deciding the treatment agent and checkup intervals in BRVO. Studies have identified factors associated with the prognosis or recurrence of BRVO using OCT and OCTA or clinical characteristics 8,[10][11][12] . EZD is associated with the degree of ischemia or prognosis in BRVO 9,13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predicting visual function and recurrence of ME is important when deciding the treatment agent and checkup intervals in BRVO. Studies have identified factors associated with the prognosis or recurrence of BRVO using OCT and OCTA or clinical characteristics 8,[10][11][12] . EZD is associated with the degree of ischemia or prognosis in BRVO 9,13 .…”
Section: Discussionmentioning
confidence: 99%
“…More studies should be conducted considering the small number of samples in previous studies including ours. Some papers have reported that baseline BCVA is good prognostic factor 10,23,24 . However, the average age is high in BRVO compared to other retinal vascular diseases and most patients diagnosed with BRVO have cataracts.…”
Section: Discussionmentioning
confidence: 99%